Estimation of cervical vertebral bone age by using mathematical formula: A cephalometric study - Bhattarai, Rashmi; Shrestha, Rabindra Man; Dhakal, Jyoti (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Craniofacial growth is an integral part of orthodontic diagnosis and treatment. Optimal effectiveness of orthodontic/orthopedic appliance is achieved during pubertal growth spurts, evaluation of maturation and growth potential is important. Radiographic assessment of hand-wrist bones is a reliable indicator of skeletal maturation, however, it requires a separate radiograph. The objective of this study was to evaluate skeletal maturation using cervical vertebral dimensions. Methods: This is an analytical cross-sectional study using lateral cephalograms of 52 subjects (26 males and 26 females). Manual tracing was done on the collected sample. Landmarks on C3 and C4 were marked. Measurement was recorded and cervical vertebral bone age was calculated by using the formula. Mandibular growth potential was calculated from cervical vertebral bone age. Paired-t test was performed to compare the cervical vertebral bone age and the chronological ages among the samples and between sexes. The correlation between the cervical vertebral bone age and the mandibular growth potential was determined by use of Pearson’s correlation coefficient. Results: The mean chronological and cervical vertebral bone age was 13.38±1.42 and 14.08±1.83 years respectively and was significant. No significant differences was found among male samples (p=0.230) whereas it was significant among females (p=0.002). A strong negative correlation was found between the cervical vertebral bone age and mandibular growth potential (r= -0.943). Linear regression equation was derived as CVBA= -4.2857+1.4286CA. Conclusions: The study showed a strong negative correlation between cervical vertebral bone age and mandibular growth potential